Salinity impacts on irrigation water-scarcity in food bowl regions of the US and Australia - Josefin Thorslund; Marc F P Bierkens; Anna Scaini; Edwin H Sutanudjaja; Michelle T H van Vliet (Environmental Research Letters, 2022)
Irrigation water use and crop production may be severely limited by both water shortages and increased salinity levels. However, impacts of crop-specific salinity limitations on irrigation water scarcity are largely unknown. We develop a salinity-inclusive water scarcity framework for the irrigation sector, accounting for crop-specific irrigation water demands and salinity tolerance levels and apply it to 29 sub-basins within two food bowl regions; the Central Valley (CV) (California) and the Murray–Darling basin (MDB) (Australia). Our results show that severe water scarcity (levels >0.4) occurs in 23% and 66% of all instances (from >17 000 monthly crop-specific estimates) for the CV and MDB, respectively. The highest water scarcity levels for both regions occurred during their summer seasons. Including salinity and crop-specific salinity tolerance levels further increased water scarcity levels, compared to estimations based on water quantity only, particularly at local sub-basin scales. We further investigate the potential of alleviating water scarcity through diluting surface water with lower saline groundwater resources, at instances where crop salinity tolerance levels are exceeded (conjunctive water use). Results from the CV highlights that conjunctive water use can reduce severe water scarcity levels by up to 67% (from 946 monthly instances where surface water salinity tolerance levels were exceeded). However, groundwater dilution requirements frequently exceed renewable groundwater rates, posing additional risks for groundwater depletion in several sub-basins. By capturing the dynamics of both crops, salinity and conjunctive water use, our framework can support local-regional agricultural and water management impacts, on water scarcity levels.